PENGARUH PEMBERIAN INSENTIF DAN FASILITAS KERJA TERHADAP SEMANGAT KERJA PERAWAT PADA RUMAH SAKIT JIWA TAMPAN RIAU (RSJT) - Suci Rahma Reza; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study aims to determine how much influence it has on the provision of work incentives and facilities on the morale of nurses at the Tampan Riau Mental Hospital. This research method is descriptive quantitative with data collection through questionnaires and interviews. The focus of sampling in this study was 60 nurses at RSJT Riau with the Probability Sampling method. The data analysis technique used is multiple linear regression analysis using SPSS 25. Based on the results of hypothesis testing, it shows that there is a partially significant effect between the provision of incentives on work morale with a tcount value of 4,316 > ttable 2,001 and facilities on the morale of RSJT nurses. Riau with a tcount of 5,137 > from ttable of 2,001. Furthermore, it is also proven that there is a simultaneous influence between the provision of incentives and work facilities to nurses at RSJT Riau with an Fcount of 16,092> from Ftable of 3.16. Among the 2 independent variables that have the strongest influence on work morale is the work facilities variable with an R Square value of 0.313. Overall, the results of the simple regression test and multiple regression were well received. Furthermore, it is recommended for the RSJ for further facilities to pay attention to providing incentives and work so that the work of nurses will increase every year, and for further research to be able to add other variables and connecting theories between variables that will be a support for researchers in order to improve knowledge. Keywords: Giving Incentives, Work Facilities, and Work Spirit.